2015
DOI: 10.5507/bp.2013.093
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of anemia in chronic kidney diseases: A review

Abstract: Backgroud. Anemia is one of the laboratory and clinical findings of chronic kidney diseases (CKD). The presence of anemia in patients with CKD has a wide range of clinically important consequences. Some of the symptoms that were previously attributed to reduced renal function are, in fact, a consequence of anemia. Anemia contributes to increased cardiac output, the development of left ventricular hypertrophy, angina, and congestive heart failure. According to current knowledge, anemia also contributes to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 58 publications
0
43
0
3
Order By: Relevance
“…Chronic anaemia, usually of the normocytic normochromic nonregenerative type, is a common and invariable complication of chronic kidney disease (CKD), resulting from decreased erythrocyte half-life, iron and folic acid deficiency, the action of uremic toxins and, especially, erythropoietin deficiency (Waki et al 2010, Macdougal 2011, Polzin 2011, Zadrazil & Horak 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic anaemia, usually of the normocytic normochromic nonregenerative type, is a common and invariable complication of chronic kidney disease (CKD), resulting from decreased erythrocyte half-life, iron and folic acid deficiency, the action of uremic toxins and, especially, erythropoietin deficiency (Waki et al 2010, Macdougal 2011, Polzin 2011, Zadrazil & Horak 2014.…”
Section: Introductionmentioning
confidence: 99%
“…2, у обстежених з ІХС та ане-мією легкого ступеня тяжкості у порівнянні із паці-єнтами контрольної групи спостерігалась активація периферійної ланки гіпоталамо-гіпофізарно-надниркової системи. Очевидно, анемія поглиблює гіпоксію, що має місце при ІХС внаслідок знижено-го серцевого викиду і недостатньої перфузії орга-нів і тканин [10], у результаті чого компенсаторно активується секреція кортизолу як основного адап-тогенного гормону в організмі людини. В подаль-шому із наростанням анемії спостерігається тенде-нція до виснаження глюкокортикоїдної функції кори надниркових залоз зі зниженням вмісту кортизолу в сироватці крові, яке, однак, не носить статистич-но вірогідний характер (р>0,05).…”
Section: роль гіперкортизолемії у прогресуванні ішемічної хвороби серunclassified
“…In the course of the inflammatory response, the absorption of iron as well as the mobilization of iron from the reticuloendothelial system, needed for erythroid cell proliferation and differentiation, is impaired, blunting, therefore, the response to rhEPO. An erythropoiesis-suppressing effect has been attributed to increased activity ofproinflammatory cytokines, and this relationship has been also proposed as a potential factor associated to rhEPO therapy resistance (2,3,5,6). Moreover, previous studies on ESRD patients showed evidence of a T-helper I polarized T-cell activation process, as well as neutrophil activation based on elastase plasma levels has also been associated with poor response to rhEPO (4).…”
mentioning
confidence: 99%
“…Nevertheless, anemia is still highly prevalent among ESRD patients and 5-10% of patients developed resistance to rhEPO therapy (2,3). This may be explained by the inflammatory response, which alters the iron metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation